Evidence of Nonadherence in Cases of Pseudoresistant Hypertension - Zanatta JMM; Cosenso-Martin LN; da Silva Lopes V; Roma Uyemura JR; Polegati Santos AM; Paz Landim MI; Yugar-Toledo JC; Vilela-Martin JF (Dove Medical Press, 2021)
João Marcos de Menezes Zanatta, Luciana Neves Cosenso-Martin, Valquíria da Silva Lopes, Jéssica Rodrigues Roma Uyemura, Aleandra Marton Polegati Santos, Manoel Ildefonso Paz Landim, Juan Carlos Yugar-Toledo, José Fernando Vilela-Martin Internal Medicine Department, State Medical School at Sao Jose Do Rio Preto (FAMERP), Sao Jose Do Rio Preto, Sao Paulo, BrazilCorrespondence: José Fernando Vilela-MartinInternal Medicine Department, State Medical School at Sao Jose Do Rio Preto (FAMERP), 5416 Avenida Brigadeiro Faria Lima, Sao Jose Do Rio Preto, SP, 15090-000, BrazilTel +55 17 3201-5727Email vilelamartin@uol.com.brAbstract: Resistant hypertension (RH) is characterized by the use of three or more antihypertensive drugs without reaching the goal of controlling blood pressure (BP). For a definitive diagnosis of RH, it is necessary to exclude causes of pseudoresistance, including the white-coat effect, errors in BP measurement, secondary hypertension, therapeutic inertia, and poor adherence to lifestyle changes and pharmacological treatment. Herein, we report the history of a patient with long-standing uncontrolled BP, even when using seven antihypertensive drugs. Causes of secondary hypertension that justified the high BP levels were investigated, in addition to the other causes of pseudo-RH. In view of the difficult-to-control BP situation, it was decided to hospitalize the patient for better investigation. After 5 days, he had BP control with practically the same medications previously used. Finally, all factors related to the presence of pseudo-RH are discussed, especially poor adherence to treatment. Poor adherence to antihypertensive treatment is common in daily medical practice, and its investigation is of fundamental importance for better management of BP.Keywords: hypertension, resistant hypertension, medication adherence